2020
DOI: 10.1177/0950017020967208
|View full text |Cite
|
Sign up to set email alerts
|

Career Advancement for Women in the British Hospitality Industry: The Enabling Factors

Abstract: Women are historically under-represented in senior management positions in almost all industries. Despite the UK hospitality industry being a major employer of women, there is a clear lack of women in management positions. This research aims to gain insight into the factors enabling women to access senior positions in the UK hospitality industry. Using the gendered organizations perspective, the study analyses female managers’ perceptions about their career advancement within this sector. It identifies key ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Strategies that enabled women to progress to senior positions include work–life balance (Lyness and Judiesch, 2014); mentoring; a range of flexible working policies (Calinaud et al , 2020); a participative leadership style promoting proactive career management initiatives (Remington and Kitterlin-Lynch, 2018); a diversity-supportive organisational culture (Sharma, 2016); diversity training (Madera, 2018); proactive and transparent gender equality measures; personal development plans (Calinaud et al , 2020); and open discussions about women’s empowerment and gender equality including accountability for gender-equal policies (Segovia-Perez et al , 2019). In addition, support for women returning from career breaks, better use of technology and flexible working (WiH2020 Review, 2019), as well as sharing of child-care responsibilities between partners, when fathers take advantage of parental leave, can help women with job stability and give them equal access to career development (Segovia-Perez et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strategies that enabled women to progress to senior positions include work–life balance (Lyness and Judiesch, 2014); mentoring; a range of flexible working policies (Calinaud et al , 2020); a participative leadership style promoting proactive career management initiatives (Remington and Kitterlin-Lynch, 2018); a diversity-supportive organisational culture (Sharma, 2016); diversity training (Madera, 2018); proactive and transparent gender equality measures; personal development plans (Calinaud et al , 2020); and open discussions about women’s empowerment and gender equality including accountability for gender-equal policies (Segovia-Perez et al , 2019). In addition, support for women returning from career breaks, better use of technology and flexible working (WiH2020 Review, 2019), as well as sharing of child-care responsibilities between partners, when fathers take advantage of parental leave, can help women with job stability and give them equal access to career development (Segovia-Perez et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical studies on career success show that men and women perceive career success in different dimensions; women tend to place more emphasis on the importance of balance and relationships, which is a subjective dimension, while men are inclined to focus on material success, which is more toward the objective dimension of career success (Mayrhofer et al, 2008 ; Afiouni and Karam, 2014 ; Hartman and Barber, 2020 ). However, there is a paucity of research on women's career progress as most studies based on the career theory do not specifically show integral gender differences in the measurement dimension related to career advancement (Calinaud et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…They find no more challenges in their job that decrease their enthusiasm in completing their work and update their profession These results were supported by De Clercq et al (2020) (35) , Hassan (2020) (19) , Ramlal and Siva (2017) (28) , and Xie et al (2016) (36) they declared that nursing staff had high level of occurrence of plateauing due to their restricted role and decrease in their engagement at work.. Moreover, Calinaudet et al (2021) (37) , Abd-Elrhamanet et al (2020) (26) , Hossain (2018) (5) , Carlson and Rotondo in Herbst-Bergin (2014) (12) found that nursing staff become highly plateaued when they weren't promoted in period from three to five years as well as their contributions weren't recognized.…”
Section: Levels Of Nursing Staff Perception Regarding Total Career Pl...mentioning
confidence: 77%